(untitled) (Nonlinear Studies, 2018)
A model of tissue formation is presented, extending M. Steinberg’s thermodynamic Differential Adhesion Mechanism to include cell membrane structures. Previous work on modeling the Margulis serial endosymbiosis theory of the origin of eukaryote cells is reviewed and a mathematical description of I.E. Wallin’s mechanism of symbioticism is presented using Finslerian anholonomic frame theory and Analytical Modular Dynamics theory for systems of second order ordinary differential equations (SODE’s). Tissues are here regarded as strained media, by analogy with continuum mechanics.